Rheophilic water mites from southern Argentina, with the description of one new genus and three new species (Acari: Hydrachnidia) - Smit, Harry (Zootaxa, 2002)
Water mites from Southern Argentinean streams, from Neuquén Province in the north to Tierra del Fuego Province in the south, were examined. One new genus is described, viz. Andesobates as well as three new species, viz. Anisitsiellides australis, Protolimnesia (Protolimnesia) pampaensis and Andesobates longipalpis. New observations are made for a number of other species, some of these new records representing a considerable range extension. Finally, additional illustrations are provided for Protolimnesia longa Besch.